2003
DOI: 10.1002/art.11251
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of HLA class II genes associated with disease susceptibility and progression in rheumatoid arthritis

Abstract: Objective. Rheumatoid arthritis (RA)-associated HLA class II genes are assumed to promote susceptibility to and/or progression of the disease. Among the various modes of action proposed so far is the effect of the differential expression of HLA class II genes in different types of antigen-presenting cells on the Th1/ Th2 balance. The aim of this study was to investigate the differential expression of genes encoded within the RA-associated HLA-DR4 superhaplotype and within the neutral DR7 and DR9 superhaplotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…A number of diseases are linked to these specificities, some of which also have clinical and pathogenetic features relevant to CSS. Among autoimmune conditions, RA is associated with HLA-DRB1*04 (35), and HLA-DRB7 has been found to correlate with the occurrence of anticardiolipin antibodies in systemic lupus erythematosus (36). Some vasculitides are also associated with such HLA alleles: giant cell arteritis is significantly associated with HLA-DRB1*04 (14).…”
Section: Discussionmentioning
confidence: 99%
“…A number of diseases are linked to these specificities, some of which also have clinical and pathogenetic features relevant to CSS. Among autoimmune conditions, RA is associated with HLA-DRB1*04 (35), and HLA-DRB7 has been found to correlate with the occurrence of anticardiolipin antibodies in systemic lupus erythematosus (36). Some vasculitides are also associated with such HLA alleles: giant cell arteritis is significantly associated with HLA-DRB1*04 (14).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this one-nucleotide difference might explain the high affinity interactions between the DRA promoter and the transcription factors RFX and NF-Y. Recently, Heldt et al (2003) demonstrated in human the functional consequences of variation close to the TATA box. Since the DNA -protein binding and functional analyses were not done in the present study, the functional role of detected polymorphisms in the promoter region in the regulation of the expression of BoLA-DRB3 gene is unknown.…”
Section: Putative Implications Of Urr-bola-drb3 Polymorphismmentioning
confidence: 97%
“…The assays used over the recent years comprise reporter constructs and RT-PCR [28], plasmon resonance combined with gel shifts [51], and FACS analysis of peripheral blood cells from donors with a restricted set of haplotypes [52]. The picture emerging is still contradictory.…”
Section: Ii) Humanmentioning
confidence: 99%